TPH2 Deficiency Influences Neuroplastic Mechanisms and Alters the Response to an Acute Stress in a Sex Specific Manner - Brivio, Paola; Sbrini, Giulia; Peeva, Polina; Todiras, Mihail; Bader, Michael; Alenina, Natalia; Calabrese, Francesca (Frontiers in Molecular Neuroscience, 2018)
Dysregulations of the central serotonergic system have been implicated in several psychopathologies, characterized by different susceptibility between males and females. We took advantage of tryptophan hydroxylase 2 (TPH2) deficient rats, lacking serotonin specifically in the brain, to investigate whether a vulnerable genotype can be associated with alterations of neuronal plasticity from the early stage of maturation of the brain until adulthood. We found a significant increase, in both gene and protein expression, of the neurotrophin, brain-derived neurotrophic factor (BDNF), in the prefrontal cortex of adult TPH2-deficient (TPH2-/-) male and female rats in comparison to wild type (TPH2+/+) counterparts. Interestingly, a development-specific pattern was observed during early postnatal life: whereas the increase in Bdnf expression, mainly driven by the modulation of Bdnf isoform IV was clearly visible after weaning at postnatal day (pnd) 30 in both sexes of TPH2-/- in comparison to TPH2+/+ rats, at early stages (pnd1 and pnd10) Bdnf expression levels did not differ between the genotypes, or even were downregulated in male TPH2-/- animals at pnd10. Moreover, to establish if hyposerotonergia may influence the response to a challenging situation, we exposed adult rats to an acute stress. Although the pattern of corticosterone release was similar between the genotypes, neuronal activation in response to stress, quantified by the expression of the immediate early genes Arc and cFos, was blunted in both sexes of animals lacking brain serotonin. Interestingly, although upregulation of Bdnf mRNA levels after stress was observed in both genotypes, it was less pronounced in TPH2-/- in comparison to TPH2+/+ rats. In summary, our results demonstrated that serotonin deficiency affects neuroplastic mechanisms following a specific temporal pattern and influences the response to an acute stress.